2022
DOI: 10.1053/j.jrn.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Measures and Lifestyle Are Associated With Deterioration in Nutritional Status in CKD Stage 4-5: The EQUAL Cohort Study

Abstract: The aim of this study was to explore the changes in nutritional status before dialysis initiation and to identify modifiable risk factors of nutritional status decline in older adults with advanced renal disease.Design and Methods: The European Quality Study on treatment in advanced chronic kidney disease (EQUAL) is a prospective, observational cohort study involving six European countries. We included 1,103 adults .65 years with incident estimated glomerular filtration rate ,20 mL/min/1.73 m 2 not on dialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Basic characteristics of the included studies are summarized in Table 1 . All except seven studies had a cross-sectional design: five were prospective cohorts [ 23 , 24 , 25 , 26 , 27 ], one a retrospective cohort [ 28 ], and one was a case-control study [ 29 ]. There were studies from each of the WHO regions: 12 from the Western Pacific Region (Australia, Brunei, China, Japan, Malaysia, and South Korea), 11 from the European Region (Belgium, Denmark, Germany, Italy, the Netherlands, Poland, Spain, Sweden, Turkey, and the United Kingdom), 6 from the Region of the Americas (Brazil, Mexico, United States), 4 from the South-East Asian Region (all from Sri Lanka), 2 from the African Region (both from Nigeria), and 2 from the Eastern Mediterranean Region (Iraq, Saudi Arabia).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Basic characteristics of the included studies are summarized in Table 1 . All except seven studies had a cross-sectional design: five were prospective cohorts [ 23 , 24 , 25 , 26 , 27 ], one a retrospective cohort [ 28 ], and one was a case-control study [ 29 ]. There were studies from each of the WHO regions: 12 from the Western Pacific Region (Australia, Brunei, China, Japan, Malaysia, and South Korea), 11 from the European Region (Belgium, Denmark, Germany, Italy, the Netherlands, Poland, Spain, Sweden, Turkey, and the United Kingdom), 6 from the Region of the Americas (Brazil, Mexico, United States), 4 from the South-East Asian Region (all from Sri Lanka), 2 from the African Region (both from Nigeria), and 2 from the Eastern Mediterranean Region (Iraq, Saudi Arabia).…”
Section: Resultsmentioning
confidence: 99%
“… a only clinical/lab/HRQoL associations with the outcome were extracted, not the prevalence or severity. b The median age and percentage of males in the EQUAL study were extracted from the article written by Windahl et al [ 23 ], whereas the number of analyzed participants was larger (data from the authors). Abbreviations: ADPKD, autosomal dominant polycystic kidney disease; AP, self-reported abdominal pain; B, self-reported bloating; BM, frequency of bowel movements; BMI, body mass index; BSFS, stool consistency according to the Bristol stool form scale; C, self-reported constipation; D, self-reported diarrhea; FC, functional constipation; FI, self-reported fecal incontinence; NR, not reported; RP, rectal pain; -s, severity of the symptom.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The articles represent data from more than 4,000 patients in whom the prevalence of sarcopenia ranged from 6% to 62% and identify a 43% increased risk of mortality associated with sarcopenia. Windahl et al 26 report on the EQUAL study and patient-reported outcomes. Their work identified that patients who reported lower physical function, more gastrointestinal symptoms, and those who were smokers had higher risk of developing malnutrition during the year of follow-up.…”
mentioning
confidence: 99%